Hadith #4919 - Sunan Abi Dawud - Abd al-Whab bin Aby عبد الوهاب بن أبي بكر; Abu al-Aswad al-Du'ali أبو الأسود الديلي/الدؤلي; al-Rabi' bin Sulaiman bin Da'ud الربيع بن سليمان بن داود; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Humaid bin 'Abdur Rahman حميد بن عبد الرحمن بن عوف الزهرى; Nafi' bin Yazid al-Kula'i نافع بن يزيد الكلاعي; Yazid bin 'Abdullah bin Usama B. al-Haad يزيد بن عبد الله بن أسامة بن الهاد (Sunan Abi Dawud)
The Prophet (ﷺ) said: Shall I not inform you of something more excellent in degree than fasting, prayer and almsgiving (sadaqah)? The people replied: Yes, Prophet of Allah! He said: It is putting things right between people, spoiling them is the shaver (destructive).
Grade: Sahih